The DoTS classification is a useful way to classify adverse drug reactions: A preliminary study in hospitalized patients (2010)
Objective The aim was to determine the prevalence of adverse drug reactions (ADRs) in hospitalized patients in a university hospital. Methods ADRs were identified by two evaluators, who reviewed the clinical histories of all patients admitted between 24 April and 24 May 2006. Patients with suspected ADRs were contacted. Three different investigators evaluated causality, the degree of preventability, and the mechanism producing the ADR. Causality was assessed using the scale proposed by the World Health Organization (WHO), and preventability was assessed using the modified Schumock and Thornton criteria. Key findings There were 32 ADRs in 104 hospitalized patients. Effects on the autonomic nervous system were the most common (13%) and the drugs most frequently implicated were systemic antimicrobial drugs (19%). Fifty-four per cent of the ADRs were classified as possible. Using the Dose, Time and Susceptibility (DoTS) classification, 77% of the ADRs were classified as being of collateral dose-responsiveness (i.e. they occurred within the range of therapeutic doses), and 65% were classified as intermediate reactions. The susceptibility factors associated most frequently with ADRs were comorbidities (i.e. the presence of diseases that were considered as risk factors to developing an ADR; 36%), age (26%) and exogenous factors (i.e. the presence of drug interactions that were involved in the occurrence of ADRs; 17%). Fifty per cent of the ADRs could have been prevented. Conclusions ADRs are very frequent in hospitalized patients and a significant proportion of them is preventable. The DoTS classification allowed complete evaluation of the types of ADR encountered. We are currently carrying out a much larger prospective study. © 2010 Royal Pharmaceutical Society of Great Britain.